Effect of baclofen on physiotherapy in the management of spastic cerebral palsy via gross motor function measure - Ali, Tabassum; Das, Bismay; Mohanty, Chhandamayee; Prasad, Rajniti; Das, B. K.; Anand, Tripti (International Journal of Research in Medical Sciences, 2020)
Background: Cerebral palsy is the most common cause of physical disability in children. The gross motor function measure-66 (GMFM-66) is an observational clinical measure designed to evaluate gross motor function in children with cerebral palsy (CP). The aim of this study was to explore pediatric physiotherapists’ experiences with the gross motor capacity with CP by implementing a short-term intervention. Methods: This study was performed in the Department of Anatomy and Department of Pediatrics, University Hospital, Banaras Hindu University, Varanasi and Kiran Society, Varanasi. Patients aged between 2 years to 14 years of both sexes satisfying the inclusion and exclusion criteria were randomly enrolled into two groups; Group A included 60 patients who received only physiotherapy and Group B included 60 patients who received baclofen along with physiotherapy. Ethical clearance was obtained from the concerned authority. Data management and statistical analysis were performed using MS excel. Results: Percentage of spastic diplegia were 20.0% and 16.6% and percentage of spastic quadriplegia were 31.6% and 26.6% in group A and group B respectively. Before treatment mean score of GMFM for group A was increased to after 3 months of treatment and which further increased to after 6 months of treatment when compared to group B as their baseline mean score of GMFM was after 3 months of treatment and it increased after 6 months of treatment. Conclusions: The findings suggest the GMFM to be a useful and reliable instrument for assessing motor function and treatment outcome in CP.